2017
DOI: 10.3399/bjgp17x691709
|View full text |Cite
|
Sign up to set email alerts
|

GPs’ mental wellbeing and psychological resources: a cross-sectional survey

Abstract: BackgroundThe negative impact of work has been the traditional focus of GP surveys. We know little about GP positive mental health and psychological resources.AimTo profile and contextualise GP positive mental health and personal psychological resources.Design and settingCross-sectional survey of GPs working in Northern Ireland (NI).MethodA questionnaire comprising the Warwick Edinburgh Mental Wellbeing Scale (WEMWBS) and measures of resilience, optimism, self-efficacy, and hope, and sociodemographic informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 74 publications
1
21
3
Order By: Relevance
“…Although the relationships between demands and resources as antecedents and burnout and work engagement as outcomes are confirmed in numerous studies, research also shows that the strength of these relationships varies. This variation is likely due to the different professional samples and work contexts that were studied 29–31. While residents and specialists work in the same occupational setting, they may face different job characteristics and, hence, different job demands and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationships between demands and resources as antecedents and burnout and work engagement as outcomes are confirmed in numerous studies, research also shows that the strength of these relationships varies. This variation is likely due to the different professional samples and work contexts that were studied 29–31. While residents and specialists work in the same occupational setting, they may face different job characteristics and, hence, different job demands and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this sample of young and future Swiss GPs reported higher mental health (52.4) compared with UK GPs (50.2), teachers (47.2), or the general population of Northern Ireland (50.8). 26 It was found that wellbeing in residents was significantly lower compared with young GPs (P<0.001); residents most often stated a lack of private time (P<0.001) and were at highest risk of burnout, when compared with GPs and medical students. These results align with findings from other studies that identified the training period as the phase most characterised by distress and difficulty.…”
Section: Comparison With Existing Literaturementioning
confidence: 90%
“…Secondly, there is risk of social desirability bias, which can potentially be lowered through anonymity of responses. 28 Thirdly, although statistical significance was found, the clinical relevance of, for example, 2 units lower in WEMWBS can be questioned; the effect sizes were, however, equal to those by Murray et al 26 The authors argue that factors such as female sex, working part-time hours, and lack of private time can accumulate (in that case to 7.6 units).…”
Section: Strengths and Limitationsmentioning
confidence: 94%
See 2 more Smart Citations